Between lives : an artist and her world - Tanning, Dorothea, 1910-2012 (New York : W. W. Norton & Company, 2001)
"Fourteen years ago, the artist Dorothea Tanning published Birthday, a collection of reminiscences. In this book, she expanded those reminiscences into a memoir of her journey through the last century as confidant, collaborator, and muse to some of its most inspired minds and personalities : a diverse assemblage that ranges from the fathers of dada and surrealism to Virgil Thompson, George Balanchine, Alberto Giacometti, Dylan Thomas, Truman Capote, Joan Miro, James Merrill, and many more. At its center is the relationship, tenderly rendered, between the author and her famed husband, the enigmatic surrealist Max Ernst."--Cover
Includes index.
Keywords: Tanning, Dorothea, -- 1910-2012; Ernst, Max, -- 1891-1976; Artists -- United States -- Biography